Associations between neutrophil percentage-to-albumin ratio with all-cause and cause-specific mortality among US cancer survivors: evidence from NHANES 2005–2018 - Wang, Mengjia; Wang, Shenkangle; Hu, Jiamiao; Wang, Xuanxuan; Pang, Yuke; Sun, Xiaonan (Frontiers in Nutrition, 2025)
BackgroundThe neutrophil percentage-to-albumin ratio (NPAR) had been suggested as a potential prognostic biomarker in various health outcomes. However, its association with mortality in cancer survivors remains unclear.MethodsA total of 3,022 cancer survivors from the National Health and Nutrition Examination Survey (NHANES) 2005–2018 were linked to mortality outcomes from the National Death Index (NDI). Weighted Cox proportional hazards models was conducted to investigate the association between NPAR and all-cause, cancer and cardiovascular disease (CVD) mortality and the hazard ratio (HR) with 95% confidence interval (CI) were calculated. Restricted cubic spline (RCS) was used to clarify the non-linear association. Additionally, analyses for stratification and sensitivity were performed.ResultsDuring a median follow-up of 75 months, 790 all-cause deaths occurred, including 244 from cancer and 209 from CVD. After adjustment for covariates, higher NPAR was independently associated with increased risk of all-cause mortality (HR = 1.09, 95% CI = 1.06–1.13), cancer mortality (HR = 1.05, 95% CI = 0.99–1.12), and CVD mortality (HR = 1.13, 95% CI = 1.06–1.21). The RCS revealed a U-shaped relationship for all-cause and cancer mortality, with thresholds of 12.76 and 13.60, respectively. Below the threshold, higher NPAR was associated with a reduced risk of mortality (HR = 0.90, 95% CI = 0.82–0.99; HR = 0.87, 95% CI = 0.76–0.99), whereas above the threshold, the risk of mortality increased significantly (HR = 1.14, 95% CI = 1.09–1.18; HR = 1.15, 95% CI = 1.07–1.24). Subgroup and sensitivity analyses confirmed these findings.ConclusionThe U-shaped association with all-cause and cancer mortality, along with the linear association with CVD mortality, underscores the potential of NPAR as a valuable prognostic marker in cancer survivors.